Media Treatment of Monetary Policy Surprises and Their Impact on Firms' and Consumers' Expectations - Julien Pinter; Evžen Kočenda (Center for Economic Studies and ifo Institute (CESifo), 2023)
Do firms' and consumers' expectations react to central bank announcements? Past literature has come to divergent conclusions, but it has systematically ignored how media treat the announcements. This paper investigates the link between monetary policy announcements and expectations by taking into account their media treatment. We initially rely on the standard monetary policy surprise measures in the euro area to identify exogenous changes in monetary policy stances. We then analyze how the main general newspapers in France report on announcements. 85 % of the monetary policy surprises are either not associated with the newspapers reporting a change in the monetary policy stance or have a sign that is inconsistent with the media report. Only when we consider media-consistent monetary policy surprises do we find that consumers and firms respond to monetary policy announcements. We then build our own measure of media monetary policy surprises and confirm that these matter. Further analysis reveals that the tonality of the media reports on the economy drives the sign of consumers' response.
Keywords: D84; E02; E52; E31; 330; firm expectations; consumer expectations; monetary policy surprises; European Central Bank; information effect